Embracing non‐Western Contexts in Management Scholarship - Wickert, Christopher; Potočnik, Kristina; Prashantham, Shameen; Shi, Weilei (Stone); Snihur, Yuliya (Journal of Management Studies, 2024)
Abstract Management is a global phenomenon. Yet, the vast majority of empirical investigations and theoretical explanations of management, managers and those being managed that are published in leading management journals are based on research that predominantly originates from Western contexts, particularly the USA and the larger European countries. Non‐Western contexts, in turn, reside at the periphery of mainstream management scholarship. This is problematic for multiple reasons. It provides an inherently limited view on the contextual factors that may explain variation in management practices across the globe, and it leads to a reductionist view of non‐Western contexts to offer little more than a means for teasing out the boundary conditions of mainstream ‘Western’ theories. This exclusion of non‐Western contexts has resulted in a marginalization of non‐Western scholarly voices, who are often hesitant to submit their research to leading scholarly journals. To address these interrelated problems, we use this introduction to the Thematic Collection on ‘Embracing non‐Western contexts’ in the Journal of Management Studies to call on scholars to more fully embrace non‐Western contexts in their research, and in doing so, to unleash the explanatory potential of these contexts for our understanding of management.